Convergence between physiological, facial and verbal self-report measures of affective empathy in children - Anastassiou-Hadjicharalambous, Xenia; Warden, David (Infant and child development, 2007)
The present study investigated the degree of convergence between three different measures of vicarious affective responsiveness (affective empathy)—verbal self‐report, facial expression and change in heart rate—in typically developing children (N=29, aged 8–10 years), when presented with an emotionally evocative film. Although convergence between physiological and verbal measures was only at chance levels, convergence between facial and physiological measures, and between facial and verbal measures was statistically significant, but low (κ=0.30 and 0.22, respectively, p<0.01). These findings have important implications for the assessment of empathy in children and indicate that generalization of results across methods should be undertaken with caution. Copyright © 2007 John Wiley & Sons, Ltd.